Inovasi Permen Daun Kelor sebagai Strategi Penguatan Santripreneur Berbasis Kearifan Lokal - Makkiyah Makkiyah; Selvi Wildatul Hamidah; Ravika Mutiara Savitrah (Ngarsa: Journal of Dedication Based on Local Wisdom, 2025)
Implementing students' entrepreneurial spirit still faces challenges, especially in product innovation and utilizing local potential. This community service presents an innovative moringa leaf candy product based on local wisdom to improve entrepreneurial skills and strengthen the santripreneur program at Al Husna Islamic Boarding School in Jember. This community service activity aims to enhance students' entrepreneurial skills and economic independence through training them to make moringa leaf candy an innovative product based on local wisdom. This community service uses an Asset-Based Community Development (ABCD) approach that emphasizes optimizing local assets owned by the Islamic boarding school, such as students' potential, and moringa plants as natural resources with economic value. The activity involves participatory training for Al Husna Islamic Boarding School students. The training material includes practical practice in making moringa leaf candy and simple marketing strategies. The community service activities included outreach on santripreneurship and the development of a santripreneur program with the innovation of moringa leaf candy. The activities ranged from briefing the students on the importance of cultivating an entrepreneurial spirit among Al Husna students to teaching them how to make moringa leaf candy as an innovation. The outreach resulted in the Al Husna Islamic Boarding School students understanding the innovation concept presented by the researcher. Keywords: Santripreneur, Innovation, Moringa Leaf Candy  Abstrak: Pelaksanaan program pengembangan jiwa kewirausahaan santri masih menghadapi tantangan, terutama dalam inovasi produk dan pemanfaatan potensi lokal. Pengabdian ini menghadirkan inovasi produk permen daun kelor berbasis kearifan lokal sebagai upaya peningkatan keterampilan kewirausahaan dan penguatan program santripreneur di Pondok Pesantren Al Husna Jember. Kegiatan pengabdian ini bertujuan untuk meningkatkan keterampilan kewirausahaan dan kemandirian ekonomi santri melalui pelatihan pembuatan permen daun kelor sebagai produk inovatif berbasis kearifan lokal. Pengabdian ini menggunakan pendekatan Asset-Based Community Development (ABCD) yang menitikberatkan pada optimalisasi aset-aset lokal yang dimiliki pesantren, seperti potensi santri, dan tanaman kelor sebagai sumber daya alam yang bernilai ekonomis. Kegiatan dilaksanakan melalui pelatihan partisipatif yang santri Pondok Pesantren Al Husna. Materi pelatihan mencakup praktik pembuatan permen daun kelor dan strategi pemasaran secara sederhana. Kegiatan pengabdian yang dilakukan meliputi penyuluhan mengenai santripreneur dan pengembangan program santripreneur dengan inovasi permen daun kelor. Kegiatan dilakukan mulai dari pengarahan kepada para santri mengenai pentingnya penanaman jiwa santripreneur pada para santri Al Husna sampai cara pembuatan permen daun kelor sebagai inovasi. Dan dari hasil penyuluan tersebut para santri pondok pesantren Al Husna dapat memahami konsep inovasi yang telah peneliti berikan. Kata kunci: Santripreneur, Inovasi, Permen Daun Kelor